Impact of Industrial Hollowing on Regional Economic Growth Rate: An Empirical Analysis based on Shanghai’s Data - Bai, Yajie; Wu, Maoguo (European Scientific Journal, ESJ, 2018)
The relation between industrial hollowing-out and Shanghai’s economic growth rate was analyzed by using ordinary least squares and ECM regression model. Data used in the empirical test was a monthly time series data from January 2003 to February 2017. Empirical results show Industrial producer price index, and the total amount of imports has a positive relationship with economic growth rate. However, fixed asset investment, land use cost, and labor resources cost have a negative impact on economic growth rate.